KAJIAN FILOSOFIS KONSEP HIGH POLITICS AMIEN RAIS DAN KORELASINYA DENGAN PENAFSIRAN BUYA HAMKA DALAM TAFSIR AL-AZHAR - Anwar, Muhammad Khoirul (STAI Asy-Syukriyyah, 2023)
This article aims to conduct a philosophical review of the concept of High Politics initiated by Amien Rais and offered to be a reference for Muhammadiyah in 1986 in organizing. The aim is to address political dynamics in Indonesia to have a moral framework in the context of following the dynamics of political progress. This paper questions the extent of this insight when viewed from the perspective of Buya Hamka’s, which is also a critical Muhammadiyah actor. Buya Hamka and Amien Rais were involved in determining Muhammadiyah to have a political view as a responsive attitude to the political dynamics of the time. This study is a literature study using Karl Menheim's sociology of knowledge approach to philosophically examine the ideas of High Politics with Hamka's political ideas when interpreting verses that contain values ​​contained in high politics. This article concludes that there is no significant difference between the high politics framework and Hamka's idea of ​​the verses used as a foothold in the high politics formula, only when Amien Rais formulates the framework, there is no opinion that refers to buya Hamka. Likewise, with Hamka there is no serious tendency in his interpretation of formulating political cases. However, both of them have the same orientation regarding the essence of politics and da'wah as a means of creating the general good and amar maruf nahi munkar. Likewise with the state system, both of them also have in common that they see the state system as taught by Islam as prioritizing deliberation or democracy and not being centralized. These two views that were born in different eras are equally intertwined with the dynamics in the Muhammadiyah organization, which is faced with an unstable political atmosphere.